Integrating climate change adaptation in coastal governance of the Barcelona metropolitan area - Inga J. Sauer; Elisabet Roca; Míriam Villares (Mitigation and Adaptation Strategies for Global Change, 2021)
Coastal cities are exposed to high risks due to climate change, as they are potentially affected by both rising sea levels and increasingly intense and frequent coastal storms. Socio-economic drivers also increase exposure to natural hazards, accelerate environmental degradation, and require adaptive governance structures to moderate negative impacts. Here, we use a social network analysis (SNA) combined with further qualitative information to identify barriers and enablers of adaptive governance in the Barcelona metropolitan area. By analyzing how climate change adaptation is mainstreamed between different administrative scales as well as different societal actors, we can determine the governance structures and external conditions that hamper or foster strategical adaptation plans from being used as operational adaptation tools. We identify a diverse set of stakeholders acting at different administrative levels (local to national), in public administration, science, civil society, and the tourism economy. The metropolitan administration acts as an important bridging organization by promoting climate change adaptation to different interest groups and by passing knowledge between actors. Nonetheless, national adaptation planning fails to take into account local experiences in coastal protection, which leads to an ineffective science policy interaction and limits adaptive management and learning opportunities. Overcoming this is difficult, however, as the effectiveness of local adaptation strategies in the Barcelona metropolitan area is very limited due to a strong centralization of power at the national level and a lack of polycentricity. Due to the high touristic pressure, the legal framework is currently oriented to primarily meet the demands of recreational use and tourism, prioritizing these aspects in daily management practice. Therefore, touristic and economic activities need to be aligned to adaptation efforts, to convert them from barriers into drivers for adaptation action. Our work strongly suggests that more effectively embedding adaptation planning and action into existing legal structures of coastal management would allow strategic adaptation plans to be an effective operational tool for local coastal governance.
Keywords: 330; Adaptive governance; Coastal hazards; Climate change adaptation; Social network analysis; Stakeholders; Barcelona metropolitan area